2020
DOI: 10.3892/etm.2020.8997
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑127‑5p attenuates severe pneumonia via tumor necrosis factor receptor‑associated factor 1

Abstract: Pneumonia is a persistent and pervasive disease, the effects of which can be severe. MicroRNA (miR)-127-5p has been utilized as a novel biomarker for the diagnosis of severe pneumonia. The present study aimed to investigate the function of miR-127-5p during severe pneumonia. An in vitro model of severe pneumonia in Ana-1 murine macrophages was established using lipopolysaccharide (LPS). Subsequently, reverse transcription-quantitative PCR and ELISA were performed to detect the mRNA and protein expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Also, miR-483 has been shown to inhibit the proliferation and migration of colorectal cancer cells by targeting TRAF1 [44]. Studies have shown that miR-127-5p alleviates severe pneumonia by targeting TRAF1 to inactivate Akt and NF-κB signaling pathways [45]. In our study, TRAF1 was con rmed as the downstream regulator of miR-378a-3p.…”
Section: Discussionsupporting
confidence: 51%
“…Also, miR-483 has been shown to inhibit the proliferation and migration of colorectal cancer cells by targeting TRAF1 [44]. Studies have shown that miR-127-5p alleviates severe pneumonia by targeting TRAF1 to inactivate Akt and NF-κB signaling pathways [45]. In our study, TRAF1 was con rmed as the downstream regulator of miR-378a-3p.…”
Section: Discussionsupporting
confidence: 51%
“…A previous study reported that miR-146b alleviates inflammation damage in pneumonia by modulating MyD88/NF-κB axis (17), suggesting that miR-146b played a protective role in pneumonia. miR-127-5p is reported to suppress pneumonia progression by downregulating TRAF1 (18), indicating that TRAF1 is a contributor in pneumonia pathology. In this study, we explored the intermolecular interaction and functional correlation between miR-146b-3p and circESPL1 or TRAF1 in pneumonia cell model.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, miR-483 has been shown to inhibit the proliferation and migration of colorectal cancer cells by targeting TRAF1 [ 42 ]. Studies have shown that miR-127-5p alleviates severe pneumonia by targeting TRAF1 to inactivate the Akt and NF-κB signaling pathways [ 43 ]. In our study, TRAF1 was confirmed as the downstream regulator of miR-378a-3p.…”
Section: Discussionmentioning
confidence: 99%